The level of preparedness of the schools for disasters from the aspect of the school principals - Ozmen, Fatma (My University, 2006)
Purpose – The purpose is, depending on the views of principals and teachers, to determine the level of preparedness of primary schools towards prospective earthquakes from the aspect of the effectiveness of school principals; and to develop some recommendations due to the obtained results and the review of the literature. Design/methodology/approach – In the research, the views of school principals and teachers were taken by a Likert type questionnaire, developed by the researcher herself. The sample of the research comprises all the elementary schools in the city centre of Elazig, a city in the Eastern Anatolian Region. As total 589 subjects responded the questionnaire. The data were computed by means of t-test, and ANOVA according to parametric or non-parametric situations. Findings – The findings have revealed that the preparedness level of the schools are not so well for prospective disasters, and there are significant differences among the views of the subjects. In other words, the school principals were not so effective in achieving high level preparedness and for prospective earthquakes. Research limitations/implications – This research is limited with the views of the teachers and of principals obtained in the city centre of Elazig. Therefore, observation-based researches may also be complementary for the reflection of the real life situation at schools. Originality/value – Although Turkey is placed a very seismically active region, the attained literature review has indicated that there have not been any researches done about the preparedness of schools for the earthquakes in Turkey, yet. Therefore, this research is an original one by obtaining the views of school teachers and of principals about the preparedness of schools towards earthquakes. © 2006, Emerald Group Publishing Limited
Keywords: Earthquakes; Natural disasters; Primary schools; Principals; Turkey